Ijtihad Hakim Peradilan Agama Bidang Hukum Kewarisan dan Kontribusinya Terhadap Hukum Nasional - Akhmad Khisni (Jurnal Hukum IUS QUIA IUSTUM, 2011)
The issues raised in this study are: The form and legal considerations, the methods and the role of ijtihad as well as the contribution of the judge ijtihad decision of religions courts in the field of inheritance law in Islamic Law Compilation (KHI)aganise the national law from the influence of muslim community life of Indonesia. The research method using a normative approach and the paradigm of constructivism, with the object research of jurisprudence of the high supreme court of Republic Indonesia and the verdict as the primary source of qualitative data analysis.  It is verdicted that: A daughter (as the inheritor) who acts hijab toward the inheritance provider’s biological brother gets all of the inheritance from the inheritance provider. This verdict seemingly confronts article 176 of Islamic Law Compilation which says:”on anly daughter alone gets a half of the inheritence …”. The verdict is the result of Ijtihad in attempt of catching the ruh (soul) or maqashid al-syari’ah in order to promote justice with a legal justification that the provider’s brother is not in responsibility for providing his niece money and other needs. It is also because of the change in social structure in farm of “family structure” which is widely known in modern Indonesian family as “nuclear family” consisting of father, mother, and children excluding relatives. This type of family structure has become more standard and socially accepted. In other words, nuclear family is a more modern model in Indonesian modern society